Students’ Perception on Online English Learning during Covid-19 Pandemic Era - Lisa Rakhmanina; Feny Martina; Friang Br Halolo; Syafryadin Syafryadin; Noermanzah Noermanzah (LP4MK STKIP PGRI Lubuklinggau, 2020)
The Covid-19 pandemic has caused schools and universities to close so that online learning is one of the solutions to prevent the spread of the Covid-19 virus. This study aims to describe students' perceptions of learning English online during the Covid-19 pandemic. This research used descriptive quantitative method. The subjects analyzed consisted of two different department groups at University of Prof. Dr. Hazairin, S.H in the 2019/2020 academic year. The number of respondents was 66 participants. The data collection technique in this study used a questionnaire distributed in the form of a Google form regarding student perceptions of the application of online English learning. The results of this study indicate that most students are interested in online learning. Online learning is considered to be more fun and flexible. In terms of the platform that is the medium for implementing online learning itself, the WhatsApp application is considered the best or dominant application and is very helpful for online learning during the pandemic. Therefore, this data proves that the research respondents had positive perceptions of online learning during the Covid-19 pandemic.